1984
DOI: 10.1042/cs0670177
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salts, Hypotension and Obstructive Jaundice

Abstract: We have examined the effects of bile duct ligation on vascular and extravascular smooth muscle responsiveness to noradrenaline and tyramine using isolated rat hindlimb perfusion, and portal vein and vas deferens preparations. Bile duct ligation reduced the contractile responses to noradrenaline of vascular and extravascular smooth muscle. Exposure of smooth muscle to some bile salts caused a reduction in contractility. This effect was dependent upon bile salt type and concentration. These studies in vitro sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 12 publications
3
38
0
1
Order By: Relevance
“…36,37) In addition, we have found that the serum concentration of nitric oxide was also elevated in patients with obstructive jaundice. Animal studies show that obstructive jaundice or isolated cholaemia produced by choleductocaval anastomosis induces arterial hypotension due to peripheral vasodilation, and blunts peripheral pressor responses to contractile substrates, [6][7][8][9][10] which are quite similar to the hemodynamic changes observed in liver cirrhosis. Thus, it is most likely that bile acids, especially chenodeoxycholic acid (free acid and its conjugates), are responsible, at least in part, for the hemodynamic changes observed in patients with hepatobiliary diseases, in which the enhancement of endothelial nitric oxide production may be involved.…”
Section: )supporting
confidence: 53%
See 1 more Smart Citation
“…36,37) In addition, we have found that the serum concentration of nitric oxide was also elevated in patients with obstructive jaundice. Animal studies show that obstructive jaundice or isolated cholaemia produced by choleductocaval anastomosis induces arterial hypotension due to peripheral vasodilation, and blunts peripheral pressor responses to contractile substrates, [6][7][8][9][10] which are quite similar to the hemodynamic changes observed in liver cirrhosis. Thus, it is most likely that bile acids, especially chenodeoxycholic acid (free acid and its conjugates), are responsible, at least in part, for the hemodynamic changes observed in patients with hepatobiliary diseases, in which the enhancement of endothelial nitric oxide production may be involved.…”
Section: )supporting
confidence: 53%
“…[1][2][3][4][5] Bile acids have been reported to exert vasoactive effects, such as vasodilatory effects. 6,7) Obstructive jaundice or isolated cholaemia produced by choleductocaval anastomosis induces arterial hypotension due to peripheral vasodilation, and peripheral pressor responses to contractile agonists are blunted. [8][9][10] In addition, in patients with liver cirrhosis, hemodynamic changes, such as arterial hypotension and reduced pressor effects of vasoconstrictor substrates, are commonly observed.…”
mentioning
confidence: 99%
“…These levels are within and even above the concentrations of bile acids shown here to enhance BK Ca channel activity and possibly con-tribute to systemic vasorelaxation. In fact, it has been suggested that increased levels of bile acids in plasma are associated with the hypotension of obstructive jaundice (Bomzon et al, 1984). There is a strong correlation between the magnitude of portosystemic shunting and elevations in plasma bile acid concentrations in portal hypertensive men (Ohkubo et al, 1984).…”
Section: Possible Role Of Bile Acid Activation Of Bk Ca Channels In Bmentioning
confidence: 99%
“…This action can explain or at least contribute to the well-known vasodilating properties and hyperkinetic circulation induced by bile acids in human pathophysiology (7). In a wide variety of human pathological conditions (8)(9)(10)(11)(12), a significant spillover of bile acids from the portal to the systemic circulation occurs, resulting in 10-to100-fold (even close to 1 mM) higher systemic bile acid concentrations (11,13,14). These levels are within and even above the concentrations of bile acids reported to enhance vascular myocyte BK Ca channel activity (4).…”
mentioning
confidence: 99%